THE INFLUENCE OF LEADERSHIP STYLE, SELF EFFICACY AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN THE PUBLIC WORKS DEPARTMENT OF MEDAN CITY - Tonny Setiawan Sinaga; Ritha F. Dalimunthe; Sukaria Sinulingga (CV. Radja Publika, 2024)
The progress of an agency is influenced by internal and external environmental factors. The extent to which the agency's goals have been achieved can be seen from how much the agency meets the demands of its environment. Meeting environmental demands means being able to take advantage of opportunities and/or overcome challenges or threats from the agency's environment. Agencies must be able to carry out various activities in order to face or meet demands and changes in the agency environment. The aim of this research is to analyze the influence of Leadership Style, Self Efficacy and Compensation on Employee Performance and Job Satisfaction in the Medan City Public Works Department. This type of research is descriptive quantitative research. The population in this research was Medan City Public Works Department employees with a total of 350 respondents. Then the sample size was determined using the Slovin formula with a sample size of 187 respondents. The sampling method used was simple random sampling. Data analysis was carried out via PLS-SEM using the Smart PLS program. The results of the research show that Leadership Style has a positive and significant effect on Employee Performance, Self Efficacy has a positive and significant effect on Employee Performance, Compensation has a positive and significant effect on Employee Performance, Leadership Style has a positive and significant effect on Job Satisfaction, Self Efficacy has a negative and insignificant effect on Job Satisfaction, Compensation has a positive and significant effect on Job Satisfaction, Job Satisfaction has a positive and significant effect on Employee Performance, Leadership Style has a positive and significant effect on Employee Performance through Job Satisfaction, Self Efficacy has a negative and insignificant effect on Employee Performance through Job Satisfaction, Compensation has a positive and significant effect on employee performance through job satisfaction.